Bibliometric Study: Writer's Productivity According to Lotka's Law in The Edulib Journal Publication Year 2011 – 2021 - Wahyudi, Agus; Junaedi, Jusa (Universitas Pendidikan Indonesia, 2023)
This research is a bibliometric study using Lotka's Law. Lotka's Law describes the frequency of publications by authors in a particular field. According to Lotka, there is an inverse relationship between the number of articles written and the number of authors who write articles, namely the more articles written, the fewer authors write them. This research aims to determine the pattern of writer productivity according to Lotka's law in the Edulib journal. The object of this research is articles in the Edulib journal with a publication period of 2011-2021. The data collection method in this research was carried out by documentation and then tabulated in table format using MS Excel. Article obtained from the page https://ejournal.upi.edu/index.php/edulib/issue/archive. The articles collected were 166 articles written by 206 different authors. In this research, the